Deliberation and scale in mekong region water governance - John Dore (2018)
Understanding the politics of deliberation, scales, and levels is crucial to understanding the social complexity of water-related governance. Deliberative processes might complement and inform more conventional representational and bureaucratic approaches to planning and decision-making. However, they are also subject to scale and level politics, which can confound institutionalized decision-making. Scale and level contests arise in dialogues and related arenas because different actors privilege particular temporal or spatial scales and levels in their analysis, arguments, and responses. Scale contests might include whether to privilege administrative, hydrological, ecosystem, or economic boundaries. Level contests might include whether to privilege the subdistrict or the province, the tributary watershed or the international river basin, a river or a biogeographic region, and the local or the regional economy. In the Mekong Region there is a recurrent demand for water resources development projects and major policies proposed by governments and investors to be scrutinized in public. Deliberative forms of engagement are potentially very helpful because they encourage supporters and critics to articulate assumptions and reasoning about the different opportunities and risks associated with alternative options, and in doing so, they often traverse and enable higher-quality conversations within and across scales and within and between levels. Six case studies from the Mekong Region are examined. We find evidence that scale and level politics affects the context, process, content, and outcomes of deliberative engagement in a region where public deliberation is still far from being a norm, particularly where there are sensitive and far-reaching choices to be made about water use and energy production. © 2010 Springer Science+Business Media, LLC.